A priori-defined Mediterranean-like dietary pattern predicts cardiovascular events better in north Europe than in Mediterranean countries. (1st May 2019) - Veglia, Fabrizio; Baldassarre, Damiano; de Faire, Ulf; Kurl, Sudhir; Smit, Andries J.; Rauramaa, Rainer; Giral, Philippe; Amato, Mauro; Di Minno, Alessandro; Ravani, Alessio; Frigerio, Beatrice; Castelnuovo, Samuela; et al.
Abstract: Background: The Mediterranean Diet (MD) is a model of healthy eating contributing to a favorable health status, but its clinical usefulness is still debated. The aim of this study was to relate the adherence to MD with the incidence of cardio/cerebro-vascular events (VEs) in north and south European participants of the IMPROVE study. Methods: IMPROVE is an observational, longitudinal, prospective cohort study involving 3703 individuals from five European countries (Finland, Sweden, Netherlands, France and Italy). The study end-point was the incidence of the first combined cardio/cerebro-vascular event occurring during 36-months follow-up. At baseline, a dietary questionnaire about the usual intake during the year preceding enrollment was administered. Based on 7 nutritional items, a MD Score was constructed in which minimal adherence was 0 and maximal adherence was 7. Results: Latitude was the strongest determinant of MD score (p < 0.001). VEs occurred in 215 participants. The incidence of VEs was the highest in subjects with MD score 0–1, lower in those with score 2–3 and the lowest in those with score ≥ 4. MD score remained significantly associated with subsequent VEs after adjustment for confounders (hazard ratio for one-point increment of the score = 0.75, p < 0.001) and the association was stronger in northern than in southern countries (p = 0.04 for MD Score × latitude interaction). Conclusions: The MD adherence score based on a simple dietary questionnaire detects changes of risk of VEs. According to our findings north Europeans appear to benefit most from VE-prevention when their diet is altered to the MD diet. Highlights: Mediterranean Diet score is able to detect changes of risk of vascular events. Latitude is the strongest determinant of Mediterranean Diet score. North Europeans are the best candidates for intervention with Mediterranean Diet.